2018
DOI: 10.1097/md.0000000000011349
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of organic cation transporter 1 (OCT1) and responses to metformin therapy in individuals with type 2 diabetes

Abstract: Background:Metformin is one of the most commonly used drugs for the treatment of type 2 diabetes mellitus (T2DM). Despite its widespread use, there are considerable interindividual variations in metformin response, with about 35% of patients failing to achieve initial glycemic control. These variabilities that reflect phenotypic differences in drug disposition and action may indeed be due to polymorphisms in genes that regulate pharmacokinetics and pharmacodynamics of metformin. Moreover, interethnic differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…In SLC22A1 gene knockout mice, the liver concentration of metformin was 30 times lower than in mice with normal functioning OCT1 transporters [ 30 ]. There were many studies of the SLC22A1 genetic polymorphisms in different populations but results on the effects of SLC22A1 polymorphisms on metformin therapeutic responses were rather contradictory [ 49 ]. Shu and colleagues suggested that genetic variation in SLC22A1 may contribute to variation in response to metformin and they performed a series of experiments to analyze whether variants rs12208357 ( R61C ), rs34130495 ( G401S ), rs72552763 ( 420del ) and rs34059508 ( G465R ) contribute to reduced therapeutic response to metformin clinically.…”
Section: Genes Associated With Metformin Responsementioning
confidence: 99%
“…In SLC22A1 gene knockout mice, the liver concentration of metformin was 30 times lower than in mice with normal functioning OCT1 transporters [ 30 ]. There were many studies of the SLC22A1 genetic polymorphisms in different populations but results on the effects of SLC22A1 polymorphisms on metformin therapeutic responses were rather contradictory [ 49 ]. Shu and colleagues suggested that genetic variation in SLC22A1 may contribute to variation in response to metformin and they performed a series of experiments to analyze whether variants rs12208357 ( R61C ), rs34130495 ( G401S ), rs72552763 ( 420del ) and rs34059508 ( G465R ) contribute to reduced therapeutic response to metformin clinically.…”
Section: Genes Associated With Metformin Responsementioning
confidence: 99%
“…Finally, genetic variation in humans may also be a confounding factor; for example, polymorphisms in the metformin transporter OCT1 have been described (as discussed earlier), with the most common being rs628031 (A > G), which reduces OCT1 expression levels and may affect uptake of metformin into tissues . Additionally, the presence of the PNPLA3 gene variant rs738409 (C > G) is associated with increased IHTAG content in humans and may also act as a confounding factor in how metformin has an impact on hepatic fat content and metabolism.…”
Section: Why Is the Literature Inconsistent?mentioning
confidence: 99%
“…It enters hepatocytes through organic cationic transporter (OCT) 1, as shown by a study demonstrating a reduced metformin uptake in hepatocytes of OCT1-deficient mice [ 28 ]. In addition, genetic polymorphisms of OCT1 in humans that determine responses to metformin have been reported [ 29 ]. Metformin is excreted via the urine, which is mediated by renal OCT1 and OCT2 on the basolateral membrane of proximal tubule cells and multidrug and toxin extrusion (MATE) 1 on the apical membrane [ 30 , 31 , 32 ].…”
Section: Glucose-lowering Mechanisms Of Metforminmentioning
confidence: 99%